2015
DOI: 10.7150/thno.11863
|View full text |Cite
|
Sign up to set email alerts
|

Single Cell Assay for Molecular Diagnostics and Medicine: Monitoring Intracellular Concentrations of Macromolecules by Two-photon Fluorescence Lifetime Imaging

Abstract: Molecular organization of a cell is dynamically transformed along the course of cellular physiological processes, pathologic developments or derived from interactions with drugs. The capability to measure and monitor concentrations of macromolecules in a single cell would greatly enhance studies of cellular processes in heterogeneous populations. In this communication, we introduce and experimentally validate a bio-analytical single-cell assay, wherein the overall concentration of macromolecules is estimated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 43 publications
5
30
0
Order By: Relevance
“…Qu's group from Shenzhen University focuses on cutting‐edge biomedical optical imaging techniques including fluorescence lifetime imaging microscopy (FLIM), super‐resolution optical imaging, nonlinear optical imaging and their applications in monitoring cell processes, cell‐drug interactions and phototherapy. With the support from the National Basic Research Program and the National Natural Science Foundation of China, Qu's group showed that fluorescence lifetime can be used to quantitatively map the local biomolecular concentration that is related to the functional and physiological state of a cell . Furthermore, they developed a rapid fluorescence lifetime imaging system (AOD‐FLIM) that is based on a pair of acousto‐optic deflectors (AOD) for the random regions of interest (ROI) study in the sample .…”
Section: Selected Research Achievementsmentioning
confidence: 99%
“…Qu's group from Shenzhen University focuses on cutting‐edge biomedical optical imaging techniques including fluorescence lifetime imaging microscopy (FLIM), super‐resolution optical imaging, nonlinear optical imaging and their applications in monitoring cell processes, cell‐drug interactions and phototherapy. With the support from the National Basic Research Program and the National Natural Science Foundation of China, Qu's group showed that fluorescence lifetime can be used to quantitatively map the local biomolecular concentration that is related to the functional and physiological state of a cell . Furthermore, they developed a rapid fluorescence lifetime imaging system (AOD‐FLIM) that is based on a pair of acousto‐optic deflectors (AOD) for the random regions of interest (ROI) study in the sample .…”
Section: Selected Research Achievementsmentioning
confidence: 99%
“…In these nuclear compartments the average protein concentration was at 284 mg/mL and 150 mg/mL, respectively. 44 …”
Section: Monitoring Intracellular Ph Level Temperature and Protein Cmentioning
confidence: 99%
“…This feature of FPs can be used for sensing changes in their environment such as intracellular pH, 39-41 temperature 42 or protein concentration. 43,44 As value of these parameters in speci¯c cellular compartments plays an important role in regulation of many intracellular processes, the reliable, accurate and noninvasive methods for Source: Reprinted by permission from Macmillan Publisher Ltd: Nature Methods, 37 Copyright 2016. determination of intracellular parameters are highly desirable in molecular biology and biomedicine. In this regard, genetically encoded FPs-based sensors have a big advantage, as they can be targeted to almost any cellular compartment without loading procedure that is required for conventional dyes.…”
Section: Monitoring Intracellular Ph Level Temperature and Protein Cmentioning
confidence: 99%
See 1 more Smart Citation
“…These features allow for°u orescence lifetime imaging microscopy (FLIM) to accurately quantitatively assess changes of many biophysical parameters of a target molecular microenvironment, such as oxygen pressure, polarity, pH, ion concentration and other biochemical parameters. 6,7 At present, the gold standard for the diagnosis of organ tissue tumors is pathological diagnosis and for cardiovascular disease, especially coronary artery disease, is angiography. However, many diagnoses of nonneoplastic diseases do not have the so-called gold standard, such as psoriasis, retinal artery occlusion, liver disease, nervous system, digestive system diseases, Alzheimer's disease, etc.…”
Section: Introductionmentioning
confidence: 99%